Al Capone does my homework [compact disc, unabridged] - Choldenko, Gennifer, 1957- (Listening Library, 2013)
"Moose Flanagan, who lives on Alcatraz along with his family and the families of the other prison guards, faces new challenges when his father is promoted to Associate Warden"--